Non-Invasive Estimation of Glioma IDH1 Mutation and VEGF Expression by Histogram Analysis of Dynamic Contrast-Enhanced MRI - Hu, Yue; Chen, Yue; Wang, Jie; Kang, Jin Juan; Shen, Dan Dan; Jia, Zhong Zheng (Frontiers in Oncology, 2020)
Objectives To investigate whether glioma isocitrate dehydrogenase (IDH) 1 mutation and vascular endothelial growth factor (VEGF) expression can be estimated by histogram analysis of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). Methods Chinese Glioma Genome Atlas (CGGA) database was wined for differential expression of VEGF in gliomas with different IDH genotypes. The VEGF expression and IDH1 genotypes of 56 glioma samples in our hospital were assessed by immunohistochemistry. Preoperative DCE-MRI data of glioma samples were reviewed. Regions of interest (ROI) covering tumor parenchyma were delineated. Histogram parameters of volume transfer constant (Ktrans) and volume of extravascular extracellular space per unit volume of tissue (Ve) derived from DCE-MRI were obtained. Histogram parameters of Ktrans, Ve and VEGF expression of IDH1 mutant type (IDH1mut) gliomas were compared with the IDH1 wildtype (IDH1wt) gliomas. Receiver operating characteristic (ROC) curve analysis was performed to differentiate IDH1mut from IDH1wt gliomas. The correlation coefficients were determined between histogram parameters of Ktrans, Ve and VEGF expression in gliomas. Results In CGGA database, VEGF expression in IDHmut gliomas was lower as compared to wildtype counterpart. The immunohistochemistry of glioma samples in our hospital also confirmed the results. Comparisons demonstrated statistically significant differences in histogram parameters of Ktrans and Ve (mean, standard deviation (SD), 50th percentile, 75th percentile, 90th percentile and 95th percentile) between IDH1mut and IDH1wt gliomas (P < 0.05, respectively). ROC curve analysis revealed that 50th percentile of Ktrans (0.019min-1) and Ve (0.039) provided the perfect combination of sensitivity and specificity in differentiating gliomas with IDH1mut from IDH1wt. Irrespective of IDH1 mutation, histogram parameters of Ktrans and Ve were correlated with VEGF expression in gliomas (P < 0.05, respectively). Conclusions VEGF expression is significantly lower in IDH1mut gliomas as compared to the wildtype counterpart and it is noninvasively predictable with histogram analysis of DCE-MRI.